Was bleibt? Zum Fortleben der DDR-Literatur in der Forschung - Kałążny, Jerzy (Studia Germanica Posnaniensia, 2017)
The title of the story What Remains by Christa Wolf denotes one of the main topics of the present discussion about German literature after 1989. The article presents the new questions (e.g. one or two German literature(s)? What does ‘GDR literature‘ mean? Is it a ‘special case’?) and changing conditions of the study of East German literature. A few new historical works discussing German literature since 1945, mainly since the reunification, and a few theoretical approaches (e.g. GDR literature as a chronotope and as regional literature) are presented.